Motivation as a Mediation on Organizational Culture and Compensation and its Effect for Performance - Novalien Carolina Lewaherilla; Victor Ernest Huwae (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2022)
This study aims to analyze the influence of organizational culture, compensation on employee performance with work motivation as a mediation. The sample taken is all employees of Bank Artha Graha as many as 31 respondents. The results of this study indicate that: (1) organizational culture has a positive and significant effect on work motivation, (2) compensation has a positive and significant effect on work motivation, (3) culture organization has a positive and insignificant effect on employee performance, (4) compensation has a positive and significant effect on employee performance, (5) work motivation has a positive and significant effect on employee performance.